Pemanfaatan Website Dalam Mengembangkan Kreatifitas Siswa Di Dunia Usaha - Ria Eka Sari; Alfa Saleh; M. Rizki Afandi (Jurnal TUNAS, 2021)
In this increasingly developing era, the internet is a medium used as a means of communication which has gradually eliminated communication media such as telephone or SMS (short message send). This is due to what has been proven that in everyday life at this time, humans are attached to a network. The development of the internet has also supported the use of computers in education. The internet can be accessed and used for various purposes, by anyone, anywhere, anytime. Various kinds of internet technology can be used, one of which is the World Wide Web (or hereinafter referred to as the "web" which is capable of providing information in the form of text, images, sound or moving images. With this capability, the web has become very popular and its development is very rapid, but generally a web like this is still static and cannot manage data. To be able to manage data in the form of a database, it is necessary to develop a web-based information system. Based on the description above, it is important to introduce the concept of a website to students, with the hope that they can take advantage and broader insight on how to create and use a website for the purpose of disseminating information to businesses.